2022
DOI: 10.1029/2022ef002748
|View full text |Cite
|
Sign up to set email alerts
|

How Much Food Can We Grow in Urban Areas? Food Production and Crop Yields of Urban Agriculture: A Meta‐Analysis

Abstract: Urban agriculture can contribute to food security, food system resilience and sustainability at the city level. While studies have examined urban agricultural productivity, we lack systemic knowledge of how agricultural productivity of urban systems compares to conventional agriculture and how productivity varies for different urban spaces (e.g., allotments vs. rooftops vs. indoor farming) and growing systems (e.g., hydroponics vs. soil‐based agriculture). Here, we present a global meta‐analysis that seeks to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 79 publications
2
26
0
2
Order By: Relevance
“…Yields for strawberries grown in UH can vary between 0.87 kg/m 2 / year for soil-based open-air cultivation (Passos et al, 2015) to 11.49 kg/m 2 /year for four stacked horizontal layers growing systems with artificial lighting (Hofkens et al, 2021). Based on 70 observations in the meta-analysis of Payen et al (2022), the average strawberry yield of UH is 2.5 kg/m 2 /year, which is similar to that expected from conventional horticulture of 2.2 kg/m 2 /year. Producing strawberries in UH could reduce the volume of imported strawberries during winter months and bring local/national strawberry production closer to all-year-round production, reducing foodmiles associated with imports.…”
Section: Strawberry As Crop For Uhmentioning
confidence: 99%
See 2 more Smart Citations
“…Yields for strawberries grown in UH can vary between 0.87 kg/m 2 / year for soil-based open-air cultivation (Passos et al, 2015) to 11.49 kg/m 2 /year for four stacked horizontal layers growing systems with artificial lighting (Hofkens et al, 2021). Based on 70 observations in the meta-analysis of Payen et al (2022), the average strawberry yield of UH is 2.5 kg/m 2 /year, which is similar to that expected from conventional horticulture of 2.2 kg/m 2 /year. Producing strawberries in UH could reduce the volume of imported strawberries during winter months and bring local/national strawberry production closer to all-year-round production, reducing foodmiles associated with imports.…”
Section: Strawberry As Crop For Uhmentioning
confidence: 99%
“…The impact of UH on the three pillars of sustainability—environment, society and economy—has been discussed by many authors (de Oliveira et al, 2020; Dorr et al, 2021; Edmondson et al, 2020; Eigenbrod & Gruda, 2015; Evans et al, 2022; Gómez et al, 2019; Kalantari et al, 2018; Khan et al, 2020; Morgan, 2014; Payen et al, 2022; Specht et al, 2015), with some variation between the spectrum of open‐air, low‐tech to indoor, high‐tech urban farms, as illustrated in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, algae can be used as mulch to retain soil moisture, which helps improve crop production. For example, it has been reported that potato yield with algae mulching was 10 times more than from the traditional farming methods in open areas [36].…”
Section: Food and Human Healthmentioning
confidence: 99%
“…Zero-energy naturally ventilated greenhouses offer higher benefits at low cost as they do not require additional heating or cooling. Greenhouses provide higher water and nutrient efficiency and can yield two to five times higher yields than outdoor horticulture production (Payen et al, 2022). Currently, 70,000 ha of the area in India is under protected cultivation.…”
Section: Introductionmentioning
confidence: 99%